Analisis Kinerja Keuangan Bank Umum Syariah pada Masa Pandemi Covid-19 Menggunakan Metode Camel (Capital, Asset Quality, Management, Earnings, Liquidity) - Fathun Ni'am Dwi Syahputra; Dwiyani Sudaryanti; Junaidi Junaidi (El-Aswaq: Islamic Economics and Finance Journal, 2022)
This research aims to determine the financial performance of Sharia Commercial Banks during COVID-19 pandemic using CAMEL method. The type of this research is descriptive analysis and uses quantitative approach. Sample of this research are 11 Sharia Commercial Banks that fulfill the criteria of research sample. The data collection technique in this research is to use secondary data in the form of quarterly financial reports of Sharia Commercial Banks for the 2020 Quarter II period to the 2021 Quarter I period. The data obtained is analyzed first with financial ratios, then the final CAMEL value is determined based on the health weight of each ratio. The ratios in this research are CAR to analyze the Capital aspect, NPF to analyze the Asset Quality aspect, NPM to analyze the Management aspect, ROA and BOPO to analyze the Earnings aspect, and FDR to analyze the Liquidity aspect. The results of this study indicate that in general the soundness of Sharia Commercial Banks during the COVID-19 pandemic (Quarter II of 2020 to Quarter I of 2021) is in the healthy criteria with an average composite value 2,1. Thus, it can be concluded that Sharia Commercial Banks are able to overcome the negative effects and economic conditions that occurred during the pandemic.